2017
DOI: 10.17265/2328-2134/2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Do Bilateral Investment Treaties Attract Foreign Direct Investment to Developing Countries? A Review of the Empirical Literature

Abstract: States have signed over 3,000 bilateral investment treaties (BITs). BITs stipulate the terms and conditions by which foreign investors from one country must be treated in another. A series of empirical studies have asked the question, do BITs increase foreign direct investment to less developed countries? This paper reviews the literature. While the studies come to conflicting results, most studies suffer from the same methodological misstep-they fail to account for variation in treaties. The paper concludes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Many empirical studies have been conducted since the 1990s. In addition, several useful survey articles have been published, including Jacobs (2017) and Pohl (2018). The results of empirical studies are mixed in that some studies found a positive impact, whereas others did not.…”
Section: Impact Of Iias On Fdi: a Survey Of Literaturementioning
confidence: 99%
“…Many empirical studies have been conducted since the 1990s. In addition, several useful survey articles have been published, including Jacobs (2017) and Pohl (2018). The results of empirical studies are mixed in that some studies found a positive impact, whereas others did not.…”
Section: Impact Of Iias On Fdi: a Survey Of Literaturementioning
confidence: 99%
“…The mixed evidence on the effects of IIAs on FDI in particular from DCs in LDCs led to doubts about the existence of the ‘grand bargain’ and the asymmetry in rent sharing between DC investors and LDC hosts (see Jacobs, 2017).…”
Section: The Literature On Iia Effects On Fdimentioning
confidence: 99%